'He Describes What He Sees': Byron's Letters from Italy. (2nd January 2017) - Howe, Anthony
Abstract: Beginning with Keats's influential snipe at Byron, 'He describes what he sees – I describe what I imagine', this essay examines Byron's ways of seeing as a writer, specifically in his letters from Italy. What emerges is a complex sense of place respecting which any simple distinction between real and imagined cannot hold. For Byron, Italy is to a striking extent a product of its successive imaginings through history. This leaves him sceptical about any authority assumed through the traveller's experience of place, and thus potentially at odds with his own privileging of being 'on the spot'. It places him, also, in an ambivalent relation to descriptive writing, which he repeatedly withholds as a correspondent.